The Effect of Firm Size, Leverage, Liquidity and Profitability on Firm Value (Empirical Study on Food and Beverage Subsector Manufacturing Companies Listed on the IDX for the 2018 – 2021 period): (Studi Empiris pada Perusahaan Manufaktur Subsektor Makanan dan Minuman Tercatat di BEI Periode 2018 – 2021) - Ramadhani, Birohmatika Nagatrahing; Wahjudi, Eko (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The purpose of this study is to evaluate and ascertain the impact of firm size, leverage, liquidity, and profitability on firm value in enterprises in the food and beverage sector listed on the Indonesia Stock Exchange (IDX). Frim size is measured using the Natural Logarithm of Total Assets (LN), leverage using the Debt to Assets Ratio (DAR), liquidity using the Current Ratio (CR), profitability using the Return On Assets (ROA) ratio, and firm value using the Price Book Value (PBV). Quantitative research is the method employed. All food and beverage companies registered on the Indonesia Stock Exchange (IDX) comprise the study's population, with an observation period running from 2018 - 2021. The sampling technique used was the purposive sampling method, so that 21 food and beverage companies were obtained that met the predetermined criteria with a total of 84 data samples used. The data source used is secondary data in the form of annual financial reports obtained from www.idx.co.id. The analytical methods used are multiple linear regression analysis, analysis of the coefficient of determination (R2 ), F statistical test, T statistical test using the SPSS application. The research results show that (1) firm size, leverage, liquidity have no effect on firm value, (2) profitability has an effect on firm value, (3) firm size, leverage, liquidity and profitability simultaneously have an effect on firm value